A study of the menstrual pattern and problems among rural school going adolescent girls of Amravati district of Maharashtra, India - Wasnik, Vinod Ramdasji; Dhumale, Digamber; Jawarkar, Ajay Keshavrao (International Journal of Research in Medical Sciences, 2017)
Background: Onset of menstruation is considered as a landmark in the growth and development of an adolescent girl. The age of onset and the pattern of menstrual cycles vary on different factors. After menarche many adolescent girls faces problems of irregular menstruation, excessive bleeding and dysmenorrhea and many more. Present study was carried in this line to find out problems. Objectives: To study the menstrual pattern & problems among school going adolescent girls in rural area of Amravati district of Maharashtra. Methods: The Prospective observational study was carried out among selected 435 Secondary and higher secondary girls students (12-16 years of age) of Ner Pinglai by purposive sampling method. The study was done in the month August 2013 to February 2014. Statistical analyses were done using SPSS 16.0 version. Results: Total 435 adolescent girls had attained menarche. The mean age of menarche was 13.5 (1.0) years. 17.9% of adolescent girls reported premenstrual syndrome. 81.3% girls had abdominal pain during menstruation followed by 28.5% cramp, 11% were uncomfortable, 11% had backache, 6.6% had headache and 2.5% girls had depression. 3.4% of the adolescent girls were did not have any symptoms during menses. Dysmenorrhoea was the most common menstrual complaint reported by 62.3% girls. 33.5 % girls have reported use of sanitary pads during menstruation. 41.6% girls have reported use of old clothes during menstruation. 21.8% had irregular menstrual cycle. Conclusion: Menstruation is an important milestone for adolescent girls and menstrual problems are common among adolescent girls. The mean age of menarche was 13.1 ± 1.0 of years. There were 1.5 menstrual symptom per adolescent girls commonest being abdominal pain. Dysmenorrhoea was seen in 62.3% of the adolescent girls. 33.5% girls have reported use of sanitary pads during menstruation. 41.6% girls have reported use of old clothes during menstruation.